2022
DOI: 10.15252/embr.202255056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into enhancement or inhibition of phase separation by different polyubiquitin chains

Abstract: Ubiquitin‐binding shuttle UBQLN2 mediates crosstalk between proteasomal degradation and autophagy, likely via interactions with K48‐ and K63‐linked polyubiquitin chains, respectively. UBQLN2 comprises self‐associating regions that drive its homotypic liquid–liquid phase separation (LLPS). Specific interactions between one of these regions and ubiquitin inhibit UBQLN2 LLPS. Here, we show that, unlike ubiquitin, the effects of multivalent polyubiquitin chains on UBQLN2 LLPS are highly dependent on chain types. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
41
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 94 publications
14
41
2
Order By: Relevance
“…This is because the microscopic interactions and mesh structure of the dense phase are both much smaller than the molecules. In agreement with this expectation, the concentration of UBQLN2 molecules in the dense phase is nearly unchanged as polyUb is added (Dao et al, 2022).…”
Section: Theory Development For How Ub Ligands Inhibit and Promote Ph...supporting
confidence: 75%
“…This is because the microscopic interactions and mesh structure of the dense phase are both much smaller than the molecules. In agreement with this expectation, the concentration of UBQLN2 molecules in the dense phase is nearly unchanged as polyUb is added (Dao et al, 2022).…”
Section: Theory Development For How Ub Ligands Inhibit and Promote Ph...supporting
confidence: 75%
“…A recent study on the effects of ubiquitin linkage type on UBQLN2 LLPS indicated that while K48-linked chains slightly promote UBQLN2 LLPS at very low Ub:UBQLN2 concentrations, most concentrations of K48-linked Ub decreased the propensity for UBQLN2 to phase separate. In contrast, K63-linked Ub had a much broader range of concentrations that promoted LLPS (Dao et al ., 2022). As E6AP is known to catalyze K48-linked ubiquitin chains, we would expect ubiquitination of a substrate by E6AP to cause its exclusion from UBQLN2 LLPS droplets.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent publication found ubiquitin chain binding to the UBQLN2 UBA induces small shifts in the NMR signals of amino acids in the region of UBQLN2 homologous to UBAA, with the magnitude of shifting dependent on chain linkage type (i.e. M1, K11, K48, K63) (Dao et al ., 2022); this finding suggests different steric hindrances from the chain type impact the amount of UBAA reorganization. Thus, either ubiquitin or E6AP AZUL binding to UBA appears to be sensed at the UBAA domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ALS-associated mutations in UBQLN2 increase oligomerization, and the ubiquitin-binding generally disrupts LLPS, droplets, and aggregates ( Dao et al, 2019 ; Zheng et al, 2021 ). The effects of polyubiquitin chains on UBQLN2 LLPS are highly dependent on the linkage-types; thus, K11- and K48-ubiquitin chains inhibit LLPS, whereas K63- and M1-ubiquitin chains, which are extended and flexible, significantly enhance UBQLN2 LLPS ( Dao et al, 2022 ). In addition to UBQLN2, K63- and M1-chains also stabilize the LLPS of p62, an UBA-containing protein ( Sun et al, 2018 ; Zaffagnini et al, 2018 ).…”
Section: Heterologous Ubiquitination and Llpsmentioning
confidence: 99%